Analysis of physicochemical and sensory properties of plant-based protein powder drinks - Odelia Sephira; Umar Lina Mardiyah; Zhe Gabrielle; Lo Diana (BIO Web of Conferences)
Protein is an essential macronutrient that plays a crucial role in maintaining body structure and supporting various physiological functions in humans. While animal products are traditionally the primary sources of dietary protein, their processing requires precise handling and they contain high levels of saturated fatty acids. As a result, plant-based protein powder drinks are gaining popularity as a healthier alternative, particularly among vegetarians, vegans, and individuals with lactose intolerance. This study aims to evaluate the physicochemical and sensory properties of plant-based protein powder drinks enriched with multigrain. The protein drinks were formulated using three different ratios: 30A70C, 20A80C, and 40A60C, where “A” represents almond powder and “C” represents cocoa powder. The physicochemical properties analyzed included color, solubility, moisture content, crude fiber, and protein content and sensory evaluation conducted using the Check-All-That-Apply (CATA) method to assess the attribute and acceptance test on aroma, taste, texture, aftertaste, and overall acceptability. The results indicated that the best formulation 20A80C had the protein content of 10.01±3.43%, with a solubility of 55.95±1.87%, moisture content of 5.92±0.43%, and crude fiber content of 3.62±0.56%. Sensory analysis using the CATA method revealed that sweet taste, savory taste, chocolate aftertaste, and chocolate aroma positively influenced the overall acceptability of the product. This study provides insights into the physicochemical characteristics and consumer preferences of plant-based protein powder drinks, highlighting their potential as a viable alternative to animal-derived milk-based products.